Gerenciamento de pontos críticos em segurança do trabalho baseado na metodologia APPCC - Macagnan, Diego Teixeira (2009)
The methodology of Hazards Analysis and Critical Control Point (HACCP), in its essence, seeks to microbial control in food. Looking for the mechanisms of its operation, this study researched possible to adapt the same as a tool to support the management of occupational risks. This work proposes to adapt the fundamentals of HACCP methodology to enable organize, identify and realize the critical control points (CCP) for the activities inherent in the process of receiving and processing of grains. In some procedures for receiving and processing were identified points of potential risks to workers. Establishing and organizing the process steps that fall as a PCA / APCC, sought to present the plan of management of critical control points for the Workers Safety (SOS Risk) with appropriate comments on each variable set. This study addresses the issue of safety. The concern with this theme, evidenced in technical publications, knowledge of cases and information acquired in test statistics on accidents at work in the country, eventually directing the study of processing enterprises of grain, in which the problems that can affect the physical integrity of workers are present at various points of the process with care and safety must be part of routine work. The basis of this study is rooted in the fundamentals of the methodology of Hazards Analysis and Critical Control Point (HACCP). The main objective of the work is to develop a method to support management of occupational risks, based on the fundamentals of HACCP methodology that is focused on the process of receiving and processing of grain, a cooperative in the industry. The research demonstrated the feasibility in use are the foundations of the HACCP approach, as a reference in developing a method (SOS Risk) for identification and risk analysis to be used in a program of management of occupational risks. The period of application to a company in the industry showed satisfactory results in a qualitative analysis. Full and rapid adaptation to the method and some issues identified in their application have been modified, added or removed from the cases analyzed for the effective safety of workers.